PHILOSOPHY OF PROGRESSIVISM AND BEYOND: TRANSFORMING CHRISTIAN RELIGIOUS EDUCATION - Alfinia Tecuari; Matthew Timothy Palit, Andani Nainggolan, Puji Efriany Zain, Lukas, Selti, Evi Mariani (Adisam Publisher, 2023)
Transforming Christian Religious Education through Philosophical Progressivism: Improving the Quality of Education and Relevance to the Contemporary Era. This research aims to examine the concept of philosophical progressivism and its application in Christian religious education in the contemporary era. The concept of philosophical progressivism has basic principles that are consistent with the goals of Christian religious education, namely to provide a holistic and critical understanding of Christianity and the surrounding environment. The results show that the application of philosophical progressivism in Christian religious education can improve the quality of education and relevance to the contemporary era. However, there are some challenges and obstacles that need to be overcome in its application. Therefore, teachers as implementers of Christian religious education need to pay attention to the basic principles of philosophical progressivism and be able to apply them in learning. This research is expected to provide recommendations for the development of Christian religious education curriculum in the future